2021
DOI: 10.1002/adma.202104174
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Optic Activity in Excess of 1000 pm V−1 Achieved via Theory‐Guided Organic Chromophore Design

Abstract: artificial intelligence/machine learning (AI/ML), cloud-based services, telemedicine, and autonomous vehicles, as well as, demands from remote work due to the COVID-19 pandemic. To keep pace with demand for optical and wireless communications, there is an urgent need for electro-optic modulators with large bandwidths, high power-efficiency, and micrometer-scale footprints that enable dense chip-scale integration with complementary metal-oxide-semiconductor electronics. [1][2][3][4] Significant improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 74 publications
0
52
0
Order By: Relevance
“…38 The study of the temporal and thermal stability of quadratic NLO response was performed by the example of P1Ch( 6) and P2Ch(6) copolymers. After storing the samples at room temperature for 3 months the measurements demonstrated almost no change in d 33 value; the heating of the samples at 50 C during 100 h also did not result in essential decrease of the NLO coefficient: 100% and 97% of the response retained for P1Ch(6) and P2Ch (6), what is better than for PMMA/AEEA-VQV-TCF and PMMA-based composite material with DBA-VQV-TCF Ar chromophoresguests. 49 The subsequent heating at 65 C during 100 h has shown that 90% and 85% of the initial NLO response retained for P1Ch(6) and P2Ch(6); the corresponding estimation for PMMA/AEEA-VQV-TCF gives 80%.…”
Section: Nlo Performancementioning
confidence: 92%
See 2 more Smart Citations
“…38 The study of the temporal and thermal stability of quadratic NLO response was performed by the example of P1Ch( 6) and P2Ch(6) copolymers. After storing the samples at room temperature for 3 months the measurements demonstrated almost no change in d 33 value; the heating of the samples at 50 C during 100 h also did not result in essential decrease of the NLO coefficient: 100% and 97% of the response retained for P1Ch(6) and P2Ch (6), what is better than for PMMA/AEEA-VQV-TCF and PMMA-based composite material with DBA-VQV-TCF Ar chromophoresguests. 49 The subsequent heating at 65 C during 100 h has shown that 90% and 85% of the initial NLO response retained for P1Ch(6) and P2Ch(6); the corresponding estimation for PMMA/AEEA-VQV-TCF gives 80%.…”
Section: Nlo Performancementioning
confidence: 92%
“…The development of organic polymer materials exhibiting quadratic nonlinear optical (NLO) response to the applied electric field during last several decades is at the forefront of research activities in the field of new functional materials, in particular, those for use in photonics and optoelectronics due to their advantages in comparison with the traditionally used inorganic materials. [1][2][3][4][5][6] High quadratic electric susceptibility, fast response, and other attractive features of these materials, together with virtually endless possibilities of structural modifications make them extremely attractive for the applications in photonic devices, such as the frequency converters, high-speed electro-optic (EO) modulators, and switches. [1][2][3]6 Polymer materials with NLO chromophores in the side chain possess a number of recognized advantages over guest-host chromophore-containing materials, the most important being enhanced NLO coefficients, improved thermal stability and temporal stability of the quadratic NLO response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] In past a decade, EO performance has been improved via strategies such as siteisolation, self-assembly, chromophore blending, and charge blocking layers (CBLs) to enhance the r N hcos 3 yi value of bulk materials. 26,28,31,33,[37][38][39][40][41][42][43][44][45][46][47][48][49] Recent work 50,51 has also shown substantial increases in hyperpolarizability due to theoryguided design, after years of little increase in b of reported chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…28 The best r 33 value (1100 AE 100 pm V À1 ) of BAH13 was achieved by using HfO 2 as CBL, which is comparable to the performance of BAY1 but with greatly decreased absorption at communication wavelengths. 50…”
Section: Introductionmentioning
confidence: 99%